Beware of the (Westernised) African eyes: rereading Psalm 82 through the vhufa approach - Ramantswana, Hulisani (Scriptura, 2017)
This article argues that the African eyes through which we are called to reread the Bible need to be decolonised on two fronts: First, our being African and being socially located in Africa does not automatically imply that we read through African eyes, so we must beware of Westernised African eyes. Second, the current post-colonial environment still retains structures of coloniality which continually destabilise Africa, so we must beware of Westernised Africa. The failure to decolonise African eyes leads to the reduplication of Western-European environments in our African context and the perpetuation of coloniality in our current environment. This article suggests the vhufa approach to reading of Scripture as a way of overcoming coloniality and as a way of bringing African knowledge systems to shape the reading of the biblical text. This approach is applied to Psalm 82 to highlight how the vhufa approach can be applied to reading of the biblical text.
free